Cinematografando o consumo :as narrativas e práticas culturais dos clientes de videolocadoras de Natal (RN) - Gomes, Jochen Mass Xavier (2005)
The present work is an exercise of analysis of cultural practices related to movie consume by the clients of video rental stores in Natal city (Rio Grande do Norte, Brazil). With sociology of practice as support, especially that one which develops from the seminal works of Anthony Giddens and Pierre Bourdieu, we have searched, from the apprehension of the narratives build up by these actors from the movies they attend, to point the way they build exercises of reflexivity and creativity in the reception of works commonly identified as products of the so called mass culture . This path allows us, in the steps of Nestor Garcia Canclini, researcher in reception within Latin-American context, create and, somehow confirm the hypothesis that consume is also useful for thinking . In order to get to this result, we have carried out a camp research that used instruments and techniques both quantitative and qualitative. After the data analysis we came to the conclusion that consume of movies taken as commercial type and as not very noble in the environment of cultural production, also impels exercises of creativity and social reflexivity